O Projeto Alfa Tuning América latina: proposta, discussões e implementação - Rueda, Jurany Leite (2017)
Considering the process of the internationalization of higher education and its regionalization beyond borders, this study had the objective of analyzing the structure of the Tuning Project in Latin America (a significant pillar derived from the European Tuning initiative, according to the principles of the Bologna Process and the European Higher Education Area), as well as learning professors‘ level of knowledge regarding adoption of the Project in the field of Education in the Brazilian context. Therefore, through a contextualized perspective regarding the knowledge of the School of Education faculty concerning the actuality of this Project in the sphere of Unicamp (The University of Campinas) – since adoption of the Project is not characterized as a State policy, but as institutional affiliation –, the progression of this research study was structured methodologically from Ball‘s Policy Cycle Approach and through qualitative research. Regarding Ball‘s Policy Cycle, three contexts were considered for the repetition of the objective: influence, production of the text and practice. The context of influence is guided by the parameters of specific political policy, the constraints and the conditions that influenced the definition, the purposes and their significance; also, in this case interest groups are identified (national and/or international). The framework of text production is based on the texts that result from the first context, among disputes, agreements, special thematic areas, time, location, the group toward which it is directed and finally the practical context – at this stage the drafted policy, with the text that explains its areas, is subject to interpretation, where it is possible to perceive its effects and consequences. From the qualitative angle, in light of content analysis considering data, a total of 17 questionnaires, which were returned, were considered from the total of 96 questionnaires that were forwarded to the School of Education professors, regarding their knowledge between adoption and/or interruption regarding the status of Unicamp in relationship to the Alfa Tuning Latin America Project. The majority of questionnaires, which were returned, demonstrated evidence that broad disclosure did not exist, so that the faculty were unable to hold a position regarding the decision of the institution in relation to adoption of the Project, or to its corresponding interruption; therefore, the majority of the faculty reported not being aware of the Project, nor knowledge of Unicamp‘s School of Education regarding adoption and/or interruption, at the same time a portion of the faculty reported partial knowledge of the Project. We understand that in the trilogy of autonomy the University must develop, the pillars over the administration, the financial area, and the pedagogical area should be analyzed and become object of intense communication through all channels, guaranteeing the main basis of democratic management.